Biosynthesis of nanoparticles using recombinant bromelain - Nasruddin, Arina; Amid, Azura; Sulaiman, Sarina; Othman, Muhd. Ezza Faiez (IIUM Press, International Islamic University Malaysia, 2018)
Green chemical method was applied to synthesize nanoparticles using recombinant bromelain. Among the numerous applications of recombinant bromelain, there is still no research on nanoparticles synthesis which encourages its utilization in this study. Four chemicals which are copper (II) chloride dihydrate (CuCl2.2H2O), cerium nitrate hexahydrate (Ce(NO3)3.6H2O), sodium selenite (Na2SeO3), and iron (III) chloride hexahydrate (FeCl3.6H2O) were selected to be screened for the suitability in nanoparticles biosynthesis by recombinant bromelain. The nanoparticles formed were characterized by using UV-visible absorption spectra. The biosynthesis process then was optimized by varying the centrifugation speed, temperature, and time to get the maximum absorption and weight of nanoparticles through central composite design (CCD) tool. Only CuCl2.2H2O showed a positive result for the screening process which was represented by the formation of colloidal solution and a maximum absorption at 580 nm. Thus, optimization was carried out for this chemical. Based on the optimization model, maximum absorption and weight were predicted at 67.5°C, 2 hrs, and 9,600 rpm. These optimal conditions were validated by repeating the biosynthesis process. The absorption and weight of the nanoparticles depended on the reaction of the chemical with recombinant bromelain. 3D plots showed that the optimal condition for high responses mostly depends on temperature and time.